2009
DOI: 10.1093/humrep/dep214
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation-induced human sperm DNA damage is predominantly mediated by oxidative stress rather than apoptosis

Abstract: Human sperm DNA fragmentation is associated with an increase in oxidative stress during cryopreservation, rather than the activation of caspases and apoptosis. The estrogenic compound genistein may be useful in reducing this effect but larger trials are needed to confirm this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
272
4
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 409 publications
(306 citation statements)
references
References 51 publications
16
272
4
14
Order By: Relevance
“…The lower DNA damage observed following supplementation of the thawing medium with genistein suggests that ROS generation and redox balance are the most important factors responsible for the disruption of the condensation and stability of sperm chromatin after cryopreservation [40]. Recently, Thomson et al [41] reported that addition of 50 µmol L -1 and 100 µmol L -1 of genistein to the cryoprotectant had a significant protective effect on sperm DNA using TUNEL and 8OHdG as a biomarker of oxidative stress and they also reported a significant Numbers with different superscripts differ significantly within the columns (P < 0.05). npg increase in motility and viability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower DNA damage observed following supplementation of the thawing medium with genistein suggests that ROS generation and redox balance are the most important factors responsible for the disruption of the condensation and stability of sperm chromatin after cryopreservation [40]. Recently, Thomson et al [41] reported that addition of 50 µmol L -1 and 100 µmol L -1 of genistein to the cryoprotectant had a significant protective effect on sperm DNA using TUNEL and 8OHdG as a biomarker of oxidative stress and they also reported a significant Numbers with different superscripts differ significantly within the columns (P < 0.05). npg increase in motility and viability.…”
Section: Resultsmentioning
confidence: 99%
“…npg increase in motility and viability. These authors concluded that human sperm DNA fragmentation is associated with an increase in oxidative stress during cryopreservation, rather than the activation of caspases and apoptosis [41].…”
Section: Resultsmentioning
confidence: 99%
“…The negative effects relating to rapid decreases in temperature, such as osmotic injury, cellular dehydration, intra-cellular ice crystal formation, and oxidative stress, also lead to damage to sperm DNA, chromatin instability and DNA denaturation [4][5][6][7][8]. Therefore, the reproductive outcome following fertilization with the sperm containing the damaged genetic material may be poor [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…For sperm cryopreservation, several factors, such as the pre-frozen sperm quality baseline, freezing and thawing method, and cryopreservative medium, and volume of cryopreserved specimen, have been previously demonstrated to be the crucial factors relating to post-thawing sperm outcome [2,7,21,23,24]. Several attempts have been made to improve cryopreservation techniques and media, leading to the improvement of cryopreservation [6,21,22,25]. Notably, the quality of ejaculated semen is also related to the outcome of cryopreservation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation